PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS KONSTRUKTIVISME PADA POKOK BAHASAN TERMOKIMIA UNTUK KELAS XI SMA/MA - ', Nurfauziah; Holiwarni, Betty; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research aims to develop Student Activities Worksheets Based on Constructivism on the Thermochemical subject valid based on the feasibility aspect of content, language, serve and graphic. The type of this research is research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student activities worksheets based on constructivism. Instrument of data collection are validation given to four validators, and from analysis data obtained by the validity of aspect of content, aspect of language, aspect of serve, and aspect of graphic are 96,43%, 97,50%, 96,88%, dan 98,44% with valid category. LKPD which validated by the validators tested to 30 students and get response result with percentage of 86,33% with positive category. Based on the result of data analysis can be concluded that student activities worksheets based on constructivism that produced is valid and can be used for the thermochemical subject for SMA/MA.Keywords: Thermochemical, Constructivism, Student Activities Worksheet